2008
DOI: 10.1002/dc.20849
|View full text |Cite
|
Sign up to set email alerts
|

Imprint cytology of high‐grade immature ovarian teratoma: A case report, literature review, and distinction from other ovarian small round cell tumors

Abstract: Immature ovarian teratoma (IOT) is a rare and aggressive malignant neoplasm characterized by immature neural tissue. The cytomorphologic features have only rarely been described. We herein describe an additional case and review the literature regarding this entity. To the best of our knowledge, this is the first reported case with imprint cytology. A 35-year-old woman presented with a pelvic mass which was resected and sent for frozen section evaluation. Imprint smears and frozen section of the mass were diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Sensitivities of frozen section diagnosis for benign, malignant and borderline ovarian epithelial tumors have been reported as 98, 88.7 and 61%, respectively [5]. The literature contains very few reports that have included information regarding ovarian germ cell tumors [8,13,14]. Pavlakis et al [11] reported that most immature teratomas were incorrectly diagnosed on frozen section examination in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivities of frozen section diagnosis for benign, malignant and borderline ovarian epithelial tumors have been reported as 98, 88.7 and 61%, respectively [5]. The literature contains very few reports that have included information regarding ovarian germ cell tumors [8,13,14]. Pavlakis et al [11] reported that most immature teratomas were incorrectly diagnosed on frozen section examination in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have detailed cytology of ovarian germ cell tumors [13,14]. In cases of low-grade immature teratoma, some frozen sections were assessed as false-negatives due to poor cellularity and poor preservation of the immature part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immaturity is usually manifested as neuroepithelium occurring either solely or in combination with immature cellular glia. 2 In adults, quantification of neural tissue is the most important factor in tumor grading and has been shown to correlate with patient's survival. 2 Immature teratoma grows rapidly, pen-etrates its capsule, and forms adhesion to surrounding structure.…”
Section: Cytologic Findingsmentioning
confidence: 99%
“…2 In adults, quantification of neural tissue is the most important factor in tumor grading and has been shown to correlate with patient's survival. 2 Immature teratoma grows rapidly, pen-etrates its capsule, and forms adhesion to surrounding structure. It metastasizes first to para aortic and pelvic lymph node and later to lung, liver, and other organ.…”
Section: Cytologic Findingsmentioning
confidence: 99%